Legal Regulation of Release of Minors From Punishment and From Service of Punishment: Foreign Experience, Administrative and Criminal Aspect - Voloshanivska, Tetiana; Nitsevych, Olesia; Morozov, Oleh; Berezniak, Vasyl; Kuznietsov, Mykola (Universitas Islam Negeri Antasari Banjarmasin, 2023)
The aim of this research is to unveil the legal regulations surrounding the release of minors from punishment and the execution of penalties. The primary focus is on investigating the efforts of European countries in establishing effective laws to prevent crimes committed by adults and to create new conditions for the rehabilitation of minors involved in criminal activities. The methodological foundation of this research is the dialectical method of scientific knowledge. Through the application of this method, the research considers the legal, functional, organizational, and procedural aspects of regulating the release of minors from punishment and punishment services. The research analyzed the general features and peculiarities of the legal regulation of coercive measures of an educational nature in several European countries, such as Germany, the Netherlands, Switzerland, Lithuania, the United Kingdom, and others. It was found that a large number of countries, in the provisions of their criminal laws, provide for the individualization and differentiation of criminal responsibility of minors, depending on various factors such as age, personality of the offender, and severity of the crime.